REPRODUCTIVE PROGRAM - THE BASE OF MODERN ORGANISATION OF AGRARIAN - INDUSTRIAL COMPLEX - Marković, Živko (Economics of Agriculture, 2006)
The base of modern organisation of agrarian-industrial complex of Serbia should consist of reproductive agrarian-industrial programms. Production capacities should adapt to these agrarian-industrial programms. Agrarian-industrial complex could be successfully constituted only if the appropriate labor sharing is done in accordance with reproductive program. Economic relationships should be established in such a way that each subjekt has economical benefits from the common labor. These economical benefits should correspond to individual contribution of each subjekt to work successfully and well. Reproductive economical connections for realizing agrarian-industrial program requires flexible organisation which is based on cooperative principles. These principles make the free unification of totaly independent economic subjects possible.